Oral Feeding of Probiotic Bifidobacterium infantis: Colonic Morphological Changes in Rat Model of TNBS-Induced Colitis - Najma H. Javed; Musaad B. Alsahly; Jagdish Khubchandani (Scientifica)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease of unknown etiology. It has been proposed that modifying the bacterial flora in intestine with probiotics may decrease the inflammatory process and prevent relapses in UC. We investigated the possible protective and therapeutic effects of a single strand of probiotic, Bifidobacterium infantis (BI), on colonic inflammation, in rats with regular feedings. Two groups of Lewis rats were prepared (n=8). The first group was the control, sham-fed group (n=4). The other group was the experimental BI-fed group (n=4). Colitis was induced in both groups by intrarectal administration of TNBS under light anesthesia. The sham-fed colitis induced groups received a daily oral gavage feeding of 1.0 mL distilled water, whereas the B. infantis-fed group received 0.205 g of B. infantis dissolved in 1.0 mL distilled water daily. The change in body weight and food and water intake was recorded over the course of each study and analyzed. The rats were euthanized and tissues from the descending colon were harvested and analyzed microscopically and histologically. Results of our study indicated significant reduction in inflammation, mucosal damage, and preservation of goblet cells, as compared to the control animals. Modulation of gastrointestinal (GI) flora suggests a promising field in developing strategies for prevention and treatment of inflammatory bowel diseases by dietary modifications.